2021
DOI: 10.1016/j.ajem.2021.02.030
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SARS and COVID-19 on major trauma in Hong Kong

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic has been enormously disruptive and harmful to people around the world, but its impact on other illnesses and injuries has been more variable. To evaluate the ramification of infectious disease outbreaks on major traumatic injuries, we compared changes in the incidence of major trauma cases during the 2003 Severe Acute Respiratory Syndrome (SARS) period with COVID-19 in 2020. Methods Data were analyzed from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 18 publications
5
25
0
Order By: Relevance
“…Some studies have reported a reduction in patient age during lockdown as well as an 8%−9.1% increase in male patients. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 18 19 20 ] In the present study, these changes were not statistically significant, supporting the published data from other studies. [ 6 10 11 18 21 ] Another important observation during the COVID-19 pandemic was a significantly prolonged time for patients to be transferred to the hospital.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Some studies have reported a reduction in patient age during lockdown as well as an 8%−9.1% increase in male patients. [ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 18 19 20 ] In the present study, these changes were not statistically significant, supporting the published data from other studies. [ 6 10 11 18 21 ] Another important observation during the COVID-19 pandemic was a significantly prolonged time for patients to be transferred to the hospital.…”
Section: Discussionsupporting
confidence: 87%
“…[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 18 19 20 ] In the present study, these changes were not statistically significant, supporting the published data from other studies. [ 6 10 11 18 21 ] Another important observation during the COVID-19 pandemic was a significantly prolonged time for patients to be transferred to the hospital. This could be due to increased concern for prehospital staff safety and the use of personal protective equipment (PPE).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations